Identifikasi Dan Prevalensi Ektoparasit Pada Sapi Di Peternakan Sapi Wilayah Kota Pekanbaru - Muhammad Ariy Naufal Pratama; Radith Mahatma (Mandalika Veterinary Journal, 2026)
The presence of ectoparasites in cattle is one of the key factors affecting livestock health and productivity. As a region with a growing small-scale cattle farming sector, Pekanbaru City requires updated information regarding the prevalence and types of ectoparasites infecting cattle. This study aims to identify ectoparasite species and determine their prevalence and infestation intensity in cattle farms across Pekanbaru. The research was conducted by manually collecting ectoparasites from 250 cattle in 11 different farms, followed by morphological identification using a microscope and analysis of prevalence and infestation intensity. Results showed that the overall ectoparasite prevalence was 20.8%, categorized as frequent, with an average infestation intensity of 3.58 individuals per animal, considered low. The identified ectoparasite species were Boophilus microplus and Rhipicephalus sanguineus. Ectoparasites were predominantly found on the cattle’s head, neck, and ears. The highest values of prevalence and intensity were recorded in specific farms with environmental conditions favorable to tick development. In conclusion, ectoparasite infestation in cattle within the Pekanbaru area is notable and requires ongoing monitoring and control, despite being in a low infestation category.